2017
DOI: 10.21767/2386-5180.1000185
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Leave Extracts of Bryophyllum pinnatum and Aspilia africana on Pathogenic Wound Isolates Recovered from Patients Admitted in University of Port Harcourt Teaching Hospital, Nigeria

Abstract: The incidence of antibiotic resistance among bacteria to synthetic drugs is on the increase, as such there is the need for new and safer antimicrobials especially, from natural sources like plants. Leaves of Bryophyllum pinnatum and Aspilia africana are among the many that have been used by rural dwellers as medicines to treat infections. Methanol, hot water and ethanolic extracts of the leaves of Bryophyllum pinnatum and Aspilia africana were obtained and their antimicrobial activity testing against three mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…Africana is scantily evident, as found in the present study, and as reported earlier (Obioma et al, 2017). No activity was recorded when the aqueous extract was used against the test bacteria.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Africana is scantily evident, as found in the present study, and as reported earlier (Obioma et al, 2017). No activity was recorded when the aqueous extract was used against the test bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…Among the extracts, A. africana's methanolic extract was the most active against P. aeruginosa. Considering the etiologic roles of P. aeruginosa in the wound and biofilmassociated infections, which risk especially increases with the prolonged use of in dwelling prosthetic and catheter devices (Dosler and Kraaslan 2014;Sharma et al, 2014;Obioma et al, 2017), the result suggests prospect of A. africana-based formulations for wound and resistance infection treatment. A similar observation of the high activity of the plant against P. aeruginosa was also, made in another study (Ezeigbo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to pomegranate ethanol extract, the methanolic extract showed the greatest antimicrobial activities against different pathogens [ 43 , 44 ]. Also, [ 45 ] recorded that the ethanol extract of Musa sapientum peel can be used to control infections caused by Saalmonella typhi and E. coli , our study showed that many pathogens were not affected by neither methanolic nor ethanolic extracts of orange or banana peels.…”
Section: Discussionmentioning
confidence: 99%
“…Kalanchoe pinnata (Akinpelu, 2000;Akinsulire et al, 2007;Gurnani et al, 2014;Kerekes et al, 2019), Cynodon dactylon (Rao et al, 2011;Abdullah et al, 2013;Chinthala et al, 2017), and Ocimum tenuiflorum (Cohen, 2014;Yamani et al, 2016), possess well-known medicinal properties, and are used for a variety of ailments in traditional medicine. Leaf extracts of these plants (methanol or ethanol-based) have been reported to have in vitro antimicrobial effects against P. aeruginosa and S. aureus, using disc-diffusion assays (Akinpelu, 2000;Agarwal et al, 2010;Rao et al, 2011;Yamani et al, 2016;Obioma et al, 2017). Therefore, these three plant-based oil formulations were determined to be scientifically sound and testable.…”
Section: Evidence Of Remedies Being Scientifically Sound and Testable In The Laboratorymentioning
confidence: 99%